PDSim: Demonstrating the capabilities of an open-source simulation framework for positive displacement compressors and expanders. (February 2020) - Ziviani, Davide; Bell, Ian H.; Zhang, Xinye; Lemort, Vincent; Paepe, Michel De; Braun, James E.; Groll, Eckhard A.
Abstract: In this paper, the first open-source generalized simulation framework for positive displacement machines (PDSim) reported in literature is employed to model different compressor and expander types. In particular, it is shown how PDSim handles specific numerical and modeling aspects common to positive displacement machines such as stiffness of differential equations, discontinuous volume curves, leakage flow models, in-chamber and shell heat transfer models, mechanical and frictional losses. A control volume approach based on a set of differential equations is used to predict the performance of different positive displacement machines under steady-periodic operations. Reciprocating, scroll, and two rotary compressors as well as a single-screw expander have been considered as examples. The source code of PDSim with examples are provided as an electronic annex.